THE EFFECT OF RETURN ON ASSET, RETURN ON EQUITY, LEVERAGE, AND EARNING PER SHARE ON COMPANY VALUE - Lutfia, Aulia Mei; Umaimah, Umaimah (Journal Universitas Muhammadiyah Gresik Engineering, Social Science, and Health International Conference (UMGESHIC); Vol 1 No 2 (2021): UMGCINMATIC : 1st Rethinking Education during Covid-19 Era: Challange and InnovationDO - 10.30587/umgeshic.v1i2.3451, 2021)
This study aims to determine how big the influence of return on assets, return on equity, leverage, earnings per share on firm value in LQ45 index companies in 2017-2020. This study uses quantitative methods and uses secondary data as a data sources. The sampling technique used purposive sampling technique and obtained data as many as 104 samples of companies. The data analysis technique used is multiple regression analysis. The results showed that return on assets variable had a significant effect on firm value. Return on equity and leverage as proxied by debt to equity ratio (DER), both have an insignificant effect on firm value. Earnings per share variable has a significant effect on firm value.